Research Progress and Future Development Trends in Medicinal Plant Transcriptomics - Guo, Junda; Huang, Zhen; Sun, Jialing; Cui, Xiuming; Liu, Yuan (Frontiers in Plant Science, 2021)
Transcriptomics is currently one of the most popular topics in biology. Transcriptome sequencing (RNA-Seq) is characterized by high throughput, high sensitivity, and high resolution, and can be used to study model and non-model organisms. Transcriptome sequencing is also an important method for studying medicinal plants due to the lack of information on their genomes. The study of medicinal plants through the transcriptomics can assist researchers in understanding the functional genes and regulatory mechanisms of medicinal plants and be helpful for breeding selection and cultivation. This article analyzes and compares the applications of transcriptome sequencing in medicinal plants over the past decade, and briefly introduces transcriptome sequencing and analysis methods, their applications in medicinal plant research, and future development trends. We will focus on the research and application progress of transcriptome sequencing in the following four areas: the mining of functional genes in medicinal plants, development of molecular markers, biosynthetic pathways of secondary metabolites, and developmental mechanisms of medicinal plants. Our study will be able to provide ideas for mining functional genes in medicinal plants and breeding new varieties.